Lipid Profiles and Body Mass Index of Senior High School Students in Northern Ghana - Seidu Sofo; Jason D. Wagganer; Thomas J. Pujol; Jeremy Barnes (Journal of Physical Education Health and Sport, 2025)
The study investigated the lipid profiles and body mass index (BMI) levels among senior high school students in Ghana. Participants were 411 students (64.96% male and 35.04% female) from two senior high schools in a municipality in the northern sector of Ghana. They comprised 41.60% Grade 10 (SHS Form 1) and 58.40% Grade 11 (SHS Form 2) students. Lipid tests and anthropometric measures were utilized to assess students’ lipid profiles and BMI. The response variables were total cholesterol (TCHOL), HDL, LDL, triglycerides (TRIG), and BMI. Students’ sex, grade level, and program of study served as predictor variables. Overall, 29.68% of the students were classified as thin or underweight, 5.60% overweight or obese, and 64.72% were in the normal BMI category. Additionally, 50.12% of the students had abnormal levels of functioning in one category, with 21.17% showing abnormal levels of functioning in at least two categories. Males had significantly higher TCHOL and LDL scores than females, while females had significantly higher BMI scores.  There were significant grade-level differences for LDL and BMI. Grade 10 students had higher LDL levels than those in Grade 11, and Grade 11 students had significantly higher BMI scores than those in Grade 10. Furthermore, there were significant differences in the programs of study for TCHOL, LDL, TRIG, and BMI.  The findings of this study underscore the need for targeted health initiatives across all programs in senior high schools, emphasizing regular health screenings for Ghanaian adolescents aimed at reducing risk for metabolic disease later in life.